Determining the predictors of physicians-in-training's willingness to refer on pharmacist- led patient medication counseling (PMC) services in selected department of a tertiary government hospital - Navarro, Diana Patrice P; Labradores, Danielle Marie C.; Pepito, Klien Jean Y.; Capule, Francis R. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2024)
Introduction: Pharmacists are essential in the provision of patient care in collaboration with other health professionals. One of their roles is to provide medication counseling to patients which makes it important to know the expectations and perceptions of physicians on this service, and how it may affect their willingness to refer their patients to such pharmacist-led patient interventions.

Objectives: The study aims to determine whether sociodemographic data, perceptions, and expectations of physicians-in-training predict their willingness to refer their patients to pharmacist-led PMC services in UP-Philippine General Hospital.

Methods: A cross-sectional study was conducted among physicians-in-training from two select departments in the UP-Philippine General Hospital from March to April 2024 by disseminating a 4-part survey questionnaire consisting of sociodemographic data, perceptions, expectations, and willingness to refer.

Results: Majority of the physicians-in-training had positive perceptions on the value of pharmacist-led PMC services (x̄ = 20.98) and competency of pharmacists providing the service (x̄ = 17.49); high expectations on the extent and accuracy of information provided by pharmacists (x̄ = 47.15); and are willing to refer their patients to the aforementioned service (98.36%). Among the variables, perceptions (p = 0.026) and expectations (p = 0.019) appear to be predictors of their willingness to refer their patients to PMC services.

Conclusion: Physicians' positive perceptions towards pharmacist-led PMC services and the competency of pharmacists providing them, as well as their high expectations on the information provided to patients during a session significantly predict their willingness to refer their patients to such pharmacist-led interventions. These findings provided a better understanding of how physicians value collaborative practice with pharmacists in enhancing patient care delivery. Further research is recommended to investigate the actual practice of referring their patients to such services.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2024
Keywords: Physicians -- Training -- Government hospitals; Referral and consultation -- Government hospitals; Pharmacist and patient -- Counseling -- Government hospitals